Influence of circadian rhythm on drug metabolism in 3D hepatic spheroids. Issue 10 (22nd July 2022) - Narayanan, Vibha; Rodrigues, Andre L.; Dordick, Jonathan S.
Abstract: Circadian rhythms are characterized as oscillations that fluctuate based on a 24 h cycle and are responsible for regulation of physiological functions. While the internal clock synchronizes gene expression using external cues like light, a similar synchronization can be induced in vitro by incubating the cells with an increased percentage of serum followed by its rapid removal. Previous studies have suggested that synchronization of HepG2 cell line induced the rhythmic expression of drug‐metabolizing enzymes (DME) most specifically the cytochrome P450 enzymes. However, there is a lack of evidence demonstrating the influence of three‐dimensional microenvironment on the rhythmicity of these genes. To understand this interplay, gene expression of the circadian machinery and CYP450s were compared using the model human hepatocarcinoma cell line, HepG2. Upon serum shock synchronization, gene and protein expression of core clock regulators was assessed and rhythmic expression of these genes was demonstrated. Further insight into the interrelations between various gene pairs was obtained using statistical analysis. Using RNA sequencing, an in‐depth understanding of the widespread effects of circadian regulation on genes involved in metabolic processes in the liver was obtained. This study aids in the better understanding of chronopharmacokinetic events in humans using physiologically relevant 3D culture systems.